2004
DOI: 10.1108/02686900410537766
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of internal audit in the private and public sectors

Abstract: This paper explores similarities and differences between public sector internal auditing and its counterpart in the private sector. Features examined include organizational status, outsourcing, using internal audit as a “tour of duty” function, activities and relationships with the external auditor. The study is based on a survey of chief internal auditors in organizations in Australia and New Zealand. Results suggest that there are differences in status between internal audit in the two sectors, with public s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
102
1
9

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(114 citation statements)
references
References 11 publications
2
102
1
9
Order By: Relevance
“…This definition signifies that internal audit has undergone a paradigm shift from an emphasis on accountability about the past to improving future outcomes to help auditees operate more effectively and efficiently (Nagy and Cenker, 2002;Stern, 1994;Goodwin, 2004). Since, the definition equally serves both the private and the public sectors (Goodwin, 2004), it is used in this study as a basis to analyse public sector internal audit effectiveness.…”
Section: Internal Audit Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…This definition signifies that internal audit has undergone a paradigm shift from an emphasis on accountability about the past to improving future outcomes to help auditees operate more effectively and efficiently (Nagy and Cenker, 2002;Stern, 1994;Goodwin, 2004). Since, the definition equally serves both the private and the public sectors (Goodwin, 2004), it is used in this study as a basis to analyse public sector internal audit effectiveness.…”
Section: Internal Audit Effectivenessmentioning
confidence: 99%
“…Since, the definition equally serves both the private and the public sectors (Goodwin, 2004), it is used in this study as a basis to analyse public sector internal audit effectiveness.…”
Section: Internal Audit Effectivenessmentioning
confidence: 99%
“…Their result indicated that 72 percent of the audit committee members were involved in the dismissal of the chief internal auditor. In a similar situation, [13] reported that 52 percent of the Australian and New Zealand audit committee members are involved in the decision to dismiss the chief internal auditor.…”
Section: Literature Reviewmentioning
confidence: 92%
“…Previous studies of [21] indicated that 69.41 percent of Italian firms do not outsourced internal audit services. Whereas, [13] indicated that 68 percent of public sector entities and 65 percent private sector entities engaged in outsourcing internal audit services.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation